Epoxy resin composition for bonding low-polarity material as well as preparation method and application of epoxy resin composition

By using an epoxy resin composition composed of matrix resin, active hydroxy polymer, surfactant and adhesion treatment agent, the problem of insufficient adhesion between epoxy resin and low-polar materials is solved, and a long storage time is achieved. Simple process and low-cost efficient bonding effect, performance exceeds that of fiberglass combined materials.

CN119192787APending Publication Date: 2024-12-27GUANGDONG HINNO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411067078.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has problems such as limited storage time, complex processing technology, high cost and low production efficiency when improving the adhesion between epoxy resin and low polar materials.

Method used

An epoxy resin composition consisting of a matrix resin, an active hydroxyl polymer containing epoxy groups, a surfactant, a coupling agent, an adhesion treatment agent and a filler is prepared by a specific proportion and process treatment. Epoxy resin compositions that bind low polarity materials with storage time, simple processing technology, low cost and high production efficiency.

Benefits of technology

Effective bonding to low-polar materials is achieved, and its performance is better than composite materials composed of glass fiber and epoxy resin, and it is cheap and has a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004979669240000091
    Figure BDA0004979669240000091
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical products, and particularly relates to an epoxy resin composition for bonding a low-polarity material and a preparation method and application thereof, the epoxy resin composition is composed of matrix resin, an active hydroxyl polymer containing an epoxy group, a surfactant, a coupling agent, an adhesion treating agent, an accelerant and a filler; the adhesive comprises the following substances in parts by weight: 30-60 parts of matrix resin, 5-15 parts of an active hydroxyl polymer containing an epoxy group, 1-3 parts of a curing agent, 5-15 parts of a surfactant, 2-4 parts of a coupling agent, 10-20 parts of an adhesive force treating agent, 0.01-0.05 part of an accelerant and 20-40 parts of filler. The method has the characteristics and effects of long storage time, simple processing technology, low cost, high production efficiency and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical products, and particularly relates to an epoxy resin composition for bonding low-polarity materials, a preparation method and application thereof. Background Art

[0002] Epoxy resin has excellent adhesion to polar substrates such as metal, cement, wood, glass, etc., and itself has good corrosion resistance and dielectric insulation. The flexibility of its use process is not available in other thermosetting plastics, so it can be made into coatings, composite materials, casting materials, adhesives, molded materials and injection molding materials, and is widely used in various fields of the national economy. However, for low-polarity materials, due to the poor adhesion of epoxy resin to the surface of low-polarity materials, it is not suitable for bonding such materials (such as UHMWPE etc.). However, UHMWPE has superior impact resistance, corrosion resistance, and absorbs impact energy. If it can be combined into composite materials with epoxy resin, its composite impact resistance will far exceed the composite material that glass fiber and epoxy resin are combined into. Therefore, it is necessary to develop a kind of epoxy resin composition that can effectively bond low-polarity materials.

[0003] At present, the methods for improving the bonding force between epoxy resin and low-polarity materials mainly include: 1. Using special solvents to corrode the surface of low-polarity materials to enhance the bonding force between low-polarity materials and epoxy resins; 2. Adding special additives to polarize low-polarity materials to enhance the bonding force between low-polarity materials and epoxy resins. For example: the invention with publication number CN114892404B relates to a method for improving the surface wettability of ultra-high molecular weight polyethylene fibers, which is a method for improving the bonding force of low-polarity materials through low-temperature plasma-polypyrrole grafting synergy, but the low-polarity materials treated by this method have the problem of limited storage time. The invention with publication number CN109096971B relates to a method for preparing a high-bonding epoxy resin composition, which is a method for improving the bonding force of low-polarity materials by adding a penetrant and a toughening agent prepared by a unique method, which has the problems of complex processing technology, high cost, and low production efficiency. Summary of the invention

[0004] One of the purposes of the present invention is to improve the bonding force of low-polarity materials and solve the problems of limited storage time or complex processing technology, high cost, low production efficiency and the like in existing methods for improving the bonding force of low-polarity materials, and to provide an epoxy resin composition for bonding low-polarity materials, which has the beneficial effects of long storage time, simple processing technology, high production efficiency and low cost.

[0005] The second purpose of the present invention is to solve the problems of limited storage time or complex processing technology, high cost and low production efficiency in the existing methods for improving the bonding strength of low-polarity materials, and to provide a method for preparing an epoxy resin composition for bonding low-polarity materials, which has the beneficial effects of long product storage time, simple processing technology, high production efficiency and low cost.

[0006] The third object of the present invention is to provide a use of an epoxy resin composition for bonding low-polarity materials, which has the beneficial effects of long product storage time, simple processing technology, high production efficiency and low cost.

[0007] In order to achieve one of the purposes of the present invention, the following technical solutions can be adopted:

[0008] An epoxy resin composition for bonding low-polarity materials, characterized in that:

[0009] It is composed of base resin, active hydroxyl polymer containing epoxy group, surfactant, coupling agent, adhesion treatment agent, accelerator and filler;

[0010] In percentage, the contents of each substance are: 30-60 parts of base resin, 5-15 parts of active hydroxyl polymer containing epoxy groups, 1-3 parts of curing agent, 5-15 parts of surfactant, 2-4 parts of coupling agent, 10-20 parts of adhesion treatment agent, 0.01-0.05 parts of accelerator, and 20-40 parts of filler.

[0011] In order to achieve one of the purposes of the present invention, the following technical solutions can also be adopted:

[0012] Furthermore, the base resin can be one or a combination of two or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin; the active hydroxyl polymer containing epoxy groups can be a polyacrylate resin modified hydroxymethyl bisphenol A epoxy resin.

[0013] Furthermore, the surfactant may be: a silanol nonionic surfactant (including polyoxyethylene alkylphenol ethers, polyoxyethylene fatty alcohol ethers or polyoxyethylene polyoxypropylene block esters), an anionic surfactant (including one or a combination of two or more of alkyl sulfates, sulfonates, fatty acids or fatty acid ester sulfates, carboxylic acid soaps, and phosphoric acid).

[0014] Furthermore, the coupling agent may be one or a combination of two or more of γ-aminopropyltriethoxysilane, γ-(2,3)epoxy(propoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0015] Furthermore, the adhesion treatment agent can be a blend of chlorinated polyethylene: rubber = 1-3:5-8; the rubber can be one or a combination of two or more of: carboxyl-terminated nitrile rubber (CTBN), isoprene rubber (IR), nitrile rubber (NBR), and hydrogenated nitrile rubber (HNBR), preferably 2:6.

[0016] Furthermore, the accelerator may be one or a combination of two or more of an imidazole accelerator, a peroxide accelerator, an azo accelerator, a tertiary amine accelerator, a phenol accelerator, an organic metal salt accelerator, and an inorganic metal salt accelerator.

[0017] Furthermore, the filler may be one or a combination of two or more of nano silicon dioxide, nano silicon powder, nano aluminum oxide, nano aluminum hydroxide, nano calcium carbonate, and nano titanium dioxide.

[0018] In order to achieve the second purpose of the present invention, the following technical solutions can be adopted:

[0019] A method for preparing an epoxy resin composition for bonding low-polarity materials, characterized in that:

[0020] 1) preparing an active hydroxyl polymer containing epoxy groups, adding methylol bisphenol A type epoxy resin, polyacrylate resin and a cosolvent into a reaction container, heating to 60-80° C. to melt; then increasing the stirring speed, stirring at high speed for 2-4 hours to obtain an active hydroxyl polymer containing epoxy groups, specifically polyacrylate resin modified methylol bisphenol A type epoxy resin;

[0021] 2) Preparing an epoxy resin composition for bonding low-polarity materials, 30-60 parts of a base resin, 5-15 parts of an active hydroxyl polymer containing epoxy groups, 1-3 parts of a curing agent, 5-15 parts of a surfactant, 2-4 parts of a coupling agent, 10-20 parts of an adhesion treatment agent, and 0.01-0.05 parts of an accelerator are put into a reactor in proportion, dispersed at high speed for 0.5 hours, and then 20-40 parts of a filler are added under stirring to prepare an epoxy resin composition adhesive for bonding low-polarity materials.

[0022] In order to achieve the second purpose of the present invention, the following technical solutions can also be adopted:

[0023] Furthermore, hydroxymethyl bisphenol A type epoxy resin is prepared by reacting hydroxymethyl bisphenol A with epichlorohydrin in the presence of an alkaline catalyst, wherein the weight ratio of hydroxymethyl bisphenol A to epichlorohydrin is 1:6-10.

[0024] Furthermore, the co-solvent is selected from one or a combination of two or more of propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, and dipropylene glycol butyl ether.

[0025] Furthermore, the curing agent is one or a combination of two or more of a cyanate curing agent, an aliphatic polyamine curing agent, an alicyclic polyamine curing agent, an aromatic amine curing agent, a polyamide curing agent and a latent curing agent.

[0026] Furthermore, the preparation method of the adhesion treatment agent is as follows: chlorinated polyethylene is completely dissolved in cyclohexanone, and rubber is completely dissolved in butanone or other solvents that can dissolve the corresponding rubber; then the above two solutions are poured into the same two bottles, fully dispersed evenly, and allowed to stand to obtain the adhesion treatment agent.

[0027] In order to achieve the third purpose of the present invention, the following technical solutions can be adopted:

[0028] A use of an epoxy resin composition for bonding low-polarity materials, characterized in that: preparing an epoxy resin composition adhesive for bonding low-polarity materials, impregnating a UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%; overlap two prepregs, cover the upper and lower sides of the laminate with a release film, place it in a programmable temperature and pressure controlled vacuum press, and press it under vacuum at 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0029] The present invention has the following beneficial effects:

[0030] 1. The epoxy resin composition for bonding low-polarity materials involved in the present invention is prepared by a special method according to a special ratio of a base resin, an active hydroxyl polymer containing epoxy groups, a surfactant, a coupling agent, an adhesion treatment agent, a promoter and a filler. Therefore, it can solve the problems of limited storage time, complex processing technology, high cost and low production efficiency in the existing methods for improving the bonding strength of low-polarity materials, and has the beneficial effects of long storage time, simple processing technology, low cost and high production efficiency.

[0031] 2. The present invention relates to a method for preparing an epoxy resin composition for bonding low-polarity materials. The method adopts two steps: first, an active hydroxyl polymer containing epoxy groups is prepared, and a hydroxymethyl bisphenol A type epoxy resin, a polyacrylate resin and a cosolvent are added to a reaction container, and the mixture is heated to 60-80° C. and melted; then, the stirring speed is increased, and the mixture is stirred at a high speed for 2-4 hours to obtain an active hydroxyl polymer containing epoxy groups, specifically a polyacrylate resin-modified hydroxymethyl bisphenol A type epoxy resin; and then, an epoxy resin composition for bonding low-polarity materials is prepared. Therefore, the method can solve the problems of limited storage time, complex processing technology, high cost, and low production efficiency in existing methods for improving the bonding strength of low-polarity materials, and has the beneficial effects of long storage time, simple processing technology, low cost, and high production efficiency.

[0032] 3. The use of the epoxy resin composition for bonding low-polar materials according to the present invention is to impregnate UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%; overlap two prepregs, cover the upper and lower sides of the laminate with a release film, place it in a programmable temperature and pressure controlled vacuum press, and press it under vacuum at 12kgf / cm 2 The product is cured at 130°C for 90 minutes under pressure conditions to produce a 0.3mm thick laminate, which has excellent impact resistance, low manufacturing cost and wide application range. Its performance far exceeds that of the composite material composed of glass fiber and epoxy resin.

[0033] 4. The present invention can well wet the low-polarity substrate without damaging the low-polarity material, and its manufacturing process is simple and low-cost. DETAILED DESCRIPTION Specific embodiment 1:

[0035] The epoxy resin composition for bonding low-polar materials involved in the specific embodiment 1 of the present invention is composed of a base resin, an active hydroxyl polymer containing epoxy groups, a surfactant, a coupling agent, an adhesion treatment agent, an accelerator and a filler;

[0036] In percentage, the contents of each substance are: 30-60 parts of base resin, 5-15 parts of active hydroxyl polymer containing epoxy groups, 1-3 parts of curing agent, 5-15 parts of surfactant, 2-4 parts of coupling agent, 10-20 parts of adhesion treatment agent, 0.01-0.05 parts of accelerator, and 20-40 parts of filler.

[0037] In this embodiment:

[0038] The base resin is bisphenol A type epoxy resin, the active hydroxy polymer containing epoxy groups is polyacrylate resin modified hydroxymethyl bisphenol A type epoxy resin, the curing agent is dicyandiamide, the surfactant is polyoxyethylene alkylphenol ether, the coupling agent is γ-aminopropyl triethoxysilane, the adhesion treatment agent is a mixture of chlorinated polyethylene and rubber blended in proportion, and the weight ratio of the two is chlorinated polyethylene: rubber = 1-3: 5-8; the accelerator is 2-methylimidazole, and the filler is nano silicon dioxide.

[0039] The preparation method of the epoxy resin composition for bonding low-polarity materials comprises the following steps:

[0040] 1) preparing an active hydroxyl polymer containing epoxy groups, adding methylol bisphenol A type epoxy resin, polyacrylate resin and a cosolvent into a reaction container, heating to 60-80° C. to melt; then increasing the stirring speed, stirring at high speed for 2-4 hours to obtain an active hydroxyl polymer containing epoxy groups, specifically polyacrylate resin modified methylol bisphenol A type epoxy resin;

[0041] 2) Preparing an epoxy resin composition for bonding low-polarity materials, 30-60 parts of a base resin, 5-15 parts of an active hydroxyl polymer containing epoxy groups, 1-3 parts of a curing agent, 5-15 parts of a surfactant, 2-4 parts of a coupling agent, 10-20 parts of an adhesion treatment agent, and 0.01-0.05 parts of an accelerator are put into a reactor in proportion, dispersed at high speed for 0.5 hours, and then 20-40 parts of a filler are added under stirring to prepare an epoxy resin composition adhesive for bonding low-polarity materials.

[0042] The use of the epoxy resin composition for bonding low-polarity materials involved in this specific embodiment 1, and the application method are as follows:

[0043] 1 part of dicyandiamide (curing agent) and 10 parts of N,N-dimethylformamide (solvent) are added to the mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin (base resin), 10 parts of active hydroxyl polymer containing epoxy groups, 10 parts of polyoxyethylene alkylphenol ether (surfactant), 2 parts of γ-aminopropyl triethoxysilane (coupling agent), 15 parts of adhesion treatment agent (adhesion treatment agent), and 0.01 parts of 2-methylimidazole (accelerator) are added in sequence under stirring. After high-speed dispersion for 0.5 hours, 30 parts of nano-silicon dioxide (filler) are added under stirring to prepare an epoxy resin composition adhesive for bonding low-polar materials. The epoxy resin composition adhesive for bonding low-polar materials is used to impregnate UHMWPE cloth (basic weight 90g / m 2), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0044] In other specific embodiments of the present invention:

[0045] Furthermore, the base resin can be one or a combination of two or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin; the active hydroxyl polymer containing epoxy groups can be a polyacrylate resin modified hydroxymethyl bisphenol A epoxy resin.

[0046] Furthermore, the surfactant may be: a silanol nonionic surfactant (including polyoxyethylene alkylphenol ethers, polyoxyethylene fatty alcohol ethers or polyoxyethylene polyoxypropylene block esters), an anionic surfactant (including one or a combination of two or more of alkyl sulfates, sulfonates, fatty acids or fatty acid ester sulfates, carboxylic acid soaps, and phosphoric acid).

[0047] Furthermore, the coupling agent may be one or a combination of two or more of γ-aminopropyltriethoxysilane, γ-(2,3)epoxy(propoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0048] Furthermore, the adhesion treatment agent can be: a mixture of chlorinated polyethylene and rubber blended in proportion, the weight ratio of the two being chlorinated polyethylene: rubber = 1-3: 5-8; the rubber can be: one or a combination of two or more of carboxyl-terminated nitrile rubber (CTBN), isoprene rubber (IR), nitrile rubber (NBR), and hydrogenated nitrile rubber (HNBR), preferably 2:6.

[0049] Furthermore, the accelerator may be one or a combination of two or more of an imidazole accelerator, a peroxide accelerator, an azo accelerator, a tertiary amine accelerator, a phenol accelerator, an organic metal salt accelerator, and an inorganic metal salt accelerator.

[0050] Furthermore, the filler may be one or a combination of two or more of nano silicon dioxide, nano silicon powder, nano aluminum oxide, nano aluminum hydroxide, nano calcium carbonate, and nano titanium dioxide.

[0051] Furthermore, hydroxymethyl bisphenol A type epoxy resin is prepared by reacting hydroxymethyl bisphenol A with epichlorohydrin in the presence of an alkaline catalyst, wherein the weight ratio of hydroxymethyl bisphenol A to epichlorohydrin is 1:6-10.

[0052] Furthermore, the co-solvent is selected from one or a combination of two or more of propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, and dipropylene glycol butyl ether.

[0053] Furthermore, the curing agent is one or a combination of two or more of a cyanate curing agent, an aliphatic polyamine curing agent, an alicyclic polyamine curing agent, an aromatic amine curing agent, a polyamide curing agent and a latent curing agent.

[0054] Furthermore, the preparation method of the adhesion treatment agent is as follows: chlorinated polyethylene is completely dissolved in cyclohexanone, and rubber is completely dissolved in butanone or other solvents that can dissolve the corresponding rubber; then the above two solutions are poured into the same two bottles, fully dispersed evenly, and allowed to stand to obtain the adhesion treatment agent.

[0055] Specific application example 1:

[0056] The application method of this specific application embodiment 1 is as follows:

[0057] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 40 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0058] Specific application example 2:

[0059] The application method of this specific application embodiment 2 is as follows:

[0060] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 50 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy groups, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent, and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring to prepare a glue solution, and the glue solution was used to impregnate UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0061] Specific application example 3:

[0062] The application method of this specific application embodiment 3 is as follows:

[0063] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 60 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0064] Specific application example 4:

[0065] The application method of this specific application embodiment 4 is as follows:

[0066] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 5 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0067] Specific application example 5:

[0068] The application method of this specific application embodiment 5 is as follows:

[0069] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 15 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0070] Specific application example 6:

[0071] The application method of this specific application embodiment 6 is as follows:

[0072] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 60 parts of bisphenol A epoxy resin, 5 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring to prepare a glue solution, and the glue solution was used to impregnate UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0073] Specific application example 7:

[0074] The application method of this specific application embodiment 7 is as follows:

[0075] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 60 parts of bisphenol A epoxy resin, 15 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring to prepare a glue solution, and the glue solution was used to impregnate UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0076] Specific application example 8:

[0077] The application method of this specific application embodiment 8 is as follows:

[0078] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 10 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0079] Specific application example 9:

[0080] The application method of this specific application embodiment 9 is as follows:

[0081] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 20 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0082] Specific application example 10:

[0083] The application method of this specific application embodiment 10 is as follows:

[0084] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 40 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 20 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0085] Specific application example 11:

[0086] The application method of this specific application embodiment 11 is as follows:

[0087] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 60 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0088] Comparative Example 1:

[0089] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 20 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and impregnated with UHMWPE cloth (basic weight 90g / m2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0090] Comparative Example 2:

[0091] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy groups, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring to prepare a glue solution, and the glue solution was used to impregnate UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0092] Comparative Example 3:

[0093] 1 part of dicyandiamide and 10 parts of N,N-dimethylformamide were added to a mixing bottle and stirred thoroughly to dissolve. Then, 30 parts of bisphenol A epoxy resin, 10 parts of active hydroxyl polymer containing epoxy group, 10 parts of polyoxyethylene alkylphenol ether, 2 parts of γ-aminopropyl triethoxysilane, 15 parts of adhesion treatment agent and 0.01 parts of 2-methylimidazole were added in sequence under stirring. After high-speed dispersion for 0.5h, 30 parts of nano-silicon dioxide were added under stirring. The glue was prepared and the UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%. Two prepregs were overlapped, and a release film was covered on each of the upper and lower sides of the laminate, and placed in a programmable temperature and pressure controlled vacuum press. In a vacuum state, the pressure was 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

[0094] The technical parameter test methods for the above application examples are as follows:

[0095] Interlayer adhesion test method: refer to IPC-TM-650 2.4.8.1.

[0096] Tensile strength test method: GB / T 1040.1-2018.

[0097] Puncture resistance test method: QC / T 744-2006 6.2.12.7.

[0098] In summary, the present invention uses an epoxy resin containing active hydroxyl groups, and the active hydroxyl groups wet the polarized UHMWPE fiber surface and form hydrogen bonds or chemical bonds, thereby improving the bonding force with UHMWPE. Due to the use of surfactants, the low-polarity substrate can be induced to polarize, so that the active hydroxyl groups of the epoxy resin have better wettability to the substrate, so that the epoxy resin substrate composition is completely wetted and close to the substrate surface before it is completely cured, thereby improving the van der Waals force (when the distance between the two planes is 1nm, the van der Waals force can reach 9.81-98.1MPa), and finally improving the adhesion of the epoxy resin composition to the substrate. Due to the use of adhesion treatment agents, the following two technical effects are achieved: 1. By improving the permeability and wettability of the epoxy resin composition and the low-polarity substrate, the epoxy resin composition is allowed to penetrate into the gaps of the substrate as much as possible, and at the same time, a three-dimensional network structure is formed on the surface of the substrate, like countless small anchors, which can firmly grasp the substrate; thereby improving the adhesion to the substrate. 2. Promote the mutual diffusion and dissolution of the epoxy resin composition and the substrate molecules, eventually leading to the disappearance of the boundary, thereby improving the adhesion between the epoxy resin composition and the substrate.

[0099] In addition, the hydroxymethyl bisphenol A type epoxy resin is prepared by reacting hydroxymethyl bisphenol A with epichlorohydrin in the presence of an alkaline catalyst; the molecular formula of the hydroxymethyl bisphenol A type epoxy resin is as follows:

[0100]

[0101] The weight ratio of hydroxymethyl bisphenol A to epichlorohydrin can be selected from 1:6-10, preferably 1:8.

[0102] The ring-opening stage is preferably carried out at a relatively low temperature (e.g., 50°C-65°C). The ring-closing reaction is an endothermic reaction, and increasing the temperature is beneficial to the reaction, and the temperature can be controlled between 75°C-80°C.

[0103] Concentration and dosage of alkaline catalyst: During ring opening, the concentration of alkaline solution can reach 30%-50%, and a smaller amount (about 1 / 10 of the amount of phenolic hydroxyl groups) can achieve a catalytic effect; during ring closing, the concentration of alkaline solution is generally 20%-30%, and the amount of alkali is roughly equivalent to the amount of chlorine atoms participating in the reaction; therefore, in general, the amount of alkali is about twice the amount of phenolic hydroxyl groups.

[0104] Preparation of polyacrylate resin modified hydroxymethyl bisphenol A type epoxy resin:

[0105] Add hydroxymethyl bisphenol A type epoxy resin, polyacrylate resin and cosolvent into a reaction container, heat to 60-80°C and melt. Increase the stirring speed and stir at high speed for 2-4 hours to obtain polyacrylate resin modified hydroxymethyl bisphenol A type epoxy resin.

[0106] The weight ratio of the hydroxymethyl bisphenol A type epoxy resin, the polyacrylate resin (solid) and the co-solvent is 10:1-3:1.

Claims

1. An epoxy resin composition for bonding low-polarity materials, characterized in that: It is composed of base resin, active hydroxyl polymer containing epoxy group, surfactant, coupling agent, adhesion treatment agent, accelerator and filler; In percentage, the contents of each substance are: 30-60 parts of base resin, 5-15 parts of active hydroxyl polymer containing epoxy groups, 1-3 parts of curing agent, 5-15 parts of surfactant, 2-4 parts of coupling agent, 10-20 parts of adhesion treatment agent, 0.01-0.05 parts of accelerator, and 20-40 parts of filler.

2. The epoxy resin composition for bonding low-polar materials according to claim 1, characterized in that: The base resin is one or a combination of two or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin; the active hydroxy polymer containing epoxy groups is polyacrylate resin modified hydroxymethyl bisphenol A epoxy resin.

3. The epoxy resin composition for bonding low-polar materials according to claim 1, characterized in that: The surfactant can be: a silanol nonionic surfactant, including polyoxyethylene alkylphenol ethers, polyoxyethylene fatty alcohol ethers or polyoxyethylene polyoxypropylene block esters, or an anionic surfactant, including one or a combination of two or more of alkyl sulfates, sulfonates, fatty acids or fatty acid ester sulfates, carboxylic acid soaps, and phosphoric acid.

4. The epoxy resin composition for bonding low-polar materials according to claim 1, characterized in that: The coupling agent is one or a combination of two or more of γ-aminopropyltriethoxysilane, γ-(2,3) epoxy(propoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; the adhesion treatment agent is a blend of chlorinated polyethylene: rubber = 1-3: 5-8; the rubber is one or a combination of two or more of terminal carboxyl nitrile rubber (CTBN), isoprene rubber (IR), nitrile rubber (NBR) and hydrogenated nitrile rubber (HNBR).

5. The epoxy resin composition for bonding low-polar materials according to claim 1, characterized in that: The accelerator is one or a combination of two or more of imidazole accelerators, peroxide accelerators, azo accelerators, tertiary amine accelerators, phenol accelerators, organic metal salt accelerators, and inorganic metal salt accelerators; the filler is one or a combination of two or more of nano silicon dioxide, nano silicon powder, nano aluminum oxide, nano aluminum hydroxide, nano calcium carbonate, and nano titanium dioxide.

6. A method for preparing an epoxy resin composition for bonding low-polarity materials, characterized in that: 1) preparing an active hydroxyl polymer containing epoxy groups, adding methylol bisphenol A type epoxy resin, polyacrylate resin and a cosolvent into a reaction container, heating to 60-80° C. to melt; then increasing the stirring speed, stirring at high speed for 2-4 hours to obtain an active hydroxyl polymer containing epoxy groups, specifically polyacrylate resin modified methylol bisphenol A type epoxy resin; 2) Preparing an epoxy resin composition for bonding low-polarity materials, 30-60 parts of a base resin, 5-15 parts of an active hydroxyl polymer containing epoxy groups, 1-3 parts of a curing agent, 5-15 parts of a surfactant, 2-4 parts of a coupling agent, 10-20 parts of an adhesion treatment agent, and 0.01-0.05 parts of an accelerator are put into a reactor in proportion, dispersed at high speed for 0.5 hours, and then 20-40 parts of a filler are added under stirring to prepare an epoxy resin composition adhesive for bonding low-polarity materials.

7. The method for preparing an epoxy resin composition for bonding low-polarity materials according to claim 6, characterized in that: The hydroxymethyl bisphenol A type epoxy resin is prepared by reacting hydroxymethyl bisphenol A with epichlorohydrin in the presence of an alkaline catalyst, wherein the weight ratio of the hydroxymethyl bisphenol A to the epichlorohydrin is 1:6-10.

8. The method for preparing an epoxy resin composition for bonding low-polarity materials according to claim 6, characterized in that: The co-solvent is selected from one or a combination of two or more of propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, and dipropylene glycol butyl ether; the curing agent is one or a combination of two or more of cyanate curing agents, fatty polyamine curing agents, alicyclic polyamine curing agents, aromatic amine curing agents, polyamide type curing agents, and latent curing agents.

9. The method for preparing an epoxy resin composition for bonding low-polarity materials according to claim 6, characterized in that: Preparation method of adhesion treatment agent: completely dissolve chlorinated polyethylene in cyclohexanone, and completely dissolve rubber in butanone or other solvents that can dissolve the corresponding rubber; then pour the above two solutions into two bottles with the same preparation, fully disperse them evenly, and let them stand to obtain the adhesion treatment agent.

10. A use of an epoxy resin composition for bonding low-polarity materials, characterized in that: Prepare an epoxy resin composition adhesive for bonding low-polarity materials, and use the epoxy resin composition adhesive to impregnate UHMWPE cloth (basic weight 90g / m 2 ), and baked in a hot air circulation oven at 130°C for 3-5 minutes to obtain a prepreg with a resin content of 41%; overlap two prepregs, cover the upper and lower sides of the laminate with a release film, place it in a programmable temperature and pressure controlled vacuum press, and press it under vacuum at 12kgf / cm 2 The product was cured at 130°C for 90 minutes under pressure conditions to produce a laminate with a thickness of 0.3 mm.

Citation Information

Patent Citations

  • A high-adhesion epoxy resin composition

    CN109096971B

  • A method for improving the surface wetting properties of ultra-high molecular weight polyethylene fibers

    CN114892404B